Clinically Relevant Concentrations of Ketamine Inhibit Osteoclast Formation In Vitro in Mouse Bone Marrow Cultures. Issue 4 (10th November 2016) - Du, Erxia; McAllister, Patrick; Venna, Venugopal Reddy; Xiao, Liping
ABSTRACT: Ketamine has been used safely in clinics for decades for analgesia and anesthesia. It is increasingly popular in clinical practice due to its new uses and importance for emergency procedures. It is known that ketamine is sequestered in the bone marrow and the major receptors for ketamine, noncompetitive N‐methyl‐d‐aspartate receptors (NMDARs), are expressed in osteoclasts (OCs) and osteoblasts. However, the impact of ketamine on OCs or osteoblasts is unknown. In this study, we investigated the effects of ketamine on osteoclastogenesis and regulation of NMDARs expression in vitro. Bone marrows (BMs) or bone marrow macrophages (BMMs) were cultured in the presence of macrophage colony‐stimulating factor (M‐CSF) and receptor activator of nuclear factor kappa‐B ligand (RANKL) with or without ketamine for up to 6 days. OC formation peaked at day 5. On day 5 of culture, ketamine inhibited OC formation from both BM and BMM cultures at clinically relevant concentrations (3–200 µM). Ketamine inhibited RANKL‐induced expression of nuclear factor of activated T‐cells, cytoplasmic, calcineurin‐dependent 1 (NFATc1) in BMM cultures. Inhibition of ketamine on RANKL‐induced osteoclastogenesis is associated with down‐regulation of NMDARs. In addition, ketamine significantly inhibited the M‐CSF induced migration of BMMs, inhibited cell fusion and significantly increased mature OC apoptosis. We conclude that clinically relevant concentrations of ketamine inhibit OC formation in both BM and BMM cultures in vitro through inhibiting migration and fusion process and enhancing mature OC apoptosis. It is likely that ketamine regulates osteoclastogenesis, at least in part, via its effects on NMDAR expression. J. Cell. Biochem. 118: 914–923, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Ketamine has been used safely in clinics for decades for analgesia and anesthesia. However, the impact of ketamine on bone cells is unknown. In this study we found clinically relevant concentrations of ketamine inhibit osteoclast formation in both BM and BMM cultures in vitro through inhibiting migration and fusion process and enhancing mature OC apoptosis. It is likely that ketamine regulates osteoclastogenesis, at least in part, via its effects on NMDAR expression.